(untitled) (Journal of Solar Energy Research Updates, 2023)
Abstract: The synthesis of blends that combine properties of two or more polymeric materials is increasingly investigated due to the versatility of the synthesis and its growing potential for many applications, including sustainability. Their characteristics are defined mainly by the synthesis conditions. Therefore, this paper details the synthesis process of easy-to-handle films using mixing method. The procedures and drawbacks found during the preparation of composite films are described. Polymeric compounds formed by the mixture of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA) are addressed, varying the concentration, and evaluating their impact on the piezoelectric capacity. Films were formed through the spin-coating technique and characterized by optical and holographic microscopes. The results showed that composites with a concentration of 50 wt.% or larger of PVDF in the blend acquire a morphology with a granular appearance, however at lower concentrations they present a homogeneous morphology similar to that of PMMA. A homogeneous distribution of PVDF in the PMMA stands out. However, excessive contents of PMMA are associated to peaks and non-uniformities detected like multicolored regions by digital holography. Controlled strength-strain laboratory tests allowed to evaluate the film blends performance. The results indicate noticeable improvements in voltage output for a composition 70wt% PVDF and 30 wt% PMMA.